Optimization of taxes and firm value: a study on tax avoidance in the food and beverage sector from the akman perspective - Irma Herliza Rizki; Mela Novita Rizki; Tina Muhardika Handayani; Muammar Rinaldi (International Journal of Applied Finance and Business Studies, 2025)
The purpose of this study is to examine the effectiveness of tax avoidance and company size in influencing firm value in the food and beverage manufacturing sector. Furthermore, the study also highlights the relevance of firm value as a contributor to broader economic growth. The research adopts a quantitative approach using secondary data collected from the Indonesia Stock Exchange (IDX). The study population consists of 26 manufacturing companies in the food and beverage subsector listed on the IDX between 2018 and 2022, with a purposive sampling method used to determine the final sample. Data were analyzed using multiple linear regression analysis, adhering to relevant statistical procedures. The findings show that both tax avoidance practices and the size of the company have a positive and significant influence on firm value. This indicates that effective tax planning, when managed responsibly, can contribute to increasing the value of a company. Additionally, larger firms with greater assets and operational scale tend to have stronger market valuations. The study underscores the importance of aligning accounting and management perspectives to optimize financial strategies that enhance firm value, particularly in the context of Indonesia's growing food and beverage industry.